2018
DOI: 10.1007/s13361-018-2115-7
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Phase Dynamics of Collision Induced Unfolding, Collision Induced Dissociation, and Electron Transfer Dissociation-Activated Polymer Ions

Abstract: Polymer characterizations are often performed using mass spectrometry (MS). Aside from MS and different tandem MS (MS/MS) techniques, ion mobility-mass spectrometry (IM-MS) has been recently added to the inventory of characterization technique. However, only few studies have focused on the reproducibility and robustness of polymer IM-MS analyses. Here, we perform collisional and electron-mediated activation of polymer ions before measuring IM drift times, collision cross-sections (CCS), or reduced ion mobiliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 74 publications
(72 reference statements)
1
5
0
Order By: Relevance
“…Most importantly, sodium adducts of poly(ethylene oxide) (PEO) exhibit robust gas‐phase structure with respect to instrumental conditions, consistent with earlier DTIMS studies that have demonstrated that the spherical shape of small PEO/Na + complexes is temperature‐independent ( vide infra ) . Similar findings regarding the conformational robustness of sodiated PEO were recently reported by Haler et al while investigating the gas‐phase dynamics of ion unfolding upon different activation methods . Moreover, Duez et al also showed a linear correlation between the CCS values derived from DTIMS experiments performed in helium and those obtained in TWIMS when using nitrogen as the drift gas .…”
Section: Methodologies In Imssupporting
confidence: 84%
“…Most importantly, sodium adducts of poly(ethylene oxide) (PEO) exhibit robust gas‐phase structure with respect to instrumental conditions, consistent with earlier DTIMS studies that have demonstrated that the spherical shape of small PEO/Na + complexes is temperature‐independent ( vide infra ) . Similar findings regarding the conformational robustness of sodiated PEO were recently reported by Haler et al while investigating the gas‐phase dynamics of ion unfolding upon different activation methods . Moreover, Duez et al also showed a linear correlation between the CCS values derived from DTIMS experiments performed in helium and those obtained in TWIMS when using nitrogen as the drift gas .…”
Section: Methodologies In Imssupporting
confidence: 84%
“…The Δ3 voltage, which was applied in the TIMS funnel 1, is useful for desolvation and declustering of ions entering the TIMS device, but may fragment or dissociate a cysteine-linked ADC if the voltage is too high. 48 This is similar to the impact that the TIMS DC gradient has on TIMS separation performance. While the Δ3 voltage and TIMS cell collision energy largely affect desolvation, the Δ6 voltage is applied at the end of the TIMS accumulation tunnel and affects the trapping and release efficiency of ions into the TIMS tunnel for separation (Figure S1).…”
Section: ■ Materials and Methodsmentioning
confidence: 56%
“…The parameters found to have the greatest impact on the TIMS separation performance were the Δ3 voltage, the Δ6 voltage, the TIMS RF, and the TIMS cell collision energy (Table S1 and Figure S1). The Δ3 voltage, which was applied in the TIMS funnel 1, is useful for desolvation and declustering of ions entering the TIMS device, but may fragment or dissociate a cysteine-linked ADC if the voltage is too high . This is similar to the impact that the TIMS DC gradient has on TIMS separation performance.…”
Section: Resultsmentioning
confidence: 99%
“…Such differences can be seen in the cation ejection species. The cation ejection species are constituted of the intact precursor ions not yet having undergone any fragmentation, but having ejected one or several sodium cations (sum of all the species; see Figure 4) [41]. Figure 4 monitors the relative intensities of the precursor ions (SY curves in Figure 2 In a Pn/i-PrOx mixture, the two polymer contributions can hence also be titrated using the cation ejection species.…”
Section: Cid Ms/ms: Cation Ejection Speciesmentioning
confidence: 99%